The added value of including key microbial traits to determine nitrogen‐related ecosystem services in managed grasslands. Issue 1 (13th November 2017) - Pommier, Thomas; Cantarel, Amélie A. M.; Grigulis, Karl; Lavorel, Sandra; Legay, Nicolas; Baxendale, Catherine; Bardgett, Richard D.; Bahn, Michael; Poly, Franck; Clément, Jean‐Christophe
Abstract: Despite playing central roles in nutrient cycles and plant growth, soil microbes are generally neglected in the study of ecosystem services (ES), due to difficulties to assess their diversity and functioning. However, to overcome these hurdles, new conceptual approaches and modern tools now provide a means to assess the role of micro‐organisms in the evaluation of ES. In managed grasslands, soil microbes are central in providing nitrogen (N)‐related ES such as maintenance of soil fertility and retention of mineral forms of N. Here, we applied state‐of‐the‐art techniques in microbial ecology and plant functional ecology to uncover the intrinsic link between N‐related bacterial functional groups, important plant functional traits, environmental factors and three proxies of maintenance of soil fertility and potential for N‐leaching across managed grasslands in three regions of Europe. By constructing well‐defined structural equation modelling, we showed that including key microbial traits improve on average more than >50% of the total variances of ES proxies, that is, ammonium ( NH 4 + ) or nitrate ( NO 3 − ) leaching, and soil organic matter content. Geographic differences arose when considering the direct relationships of these ES proxies with specific microbial traits: nitrate leaching was positively correlated to the maximum rate of nitrification, except in the Austrian site and potentially leached NH 4 + –N was negatively correlated to the fungi/bacteria ratio, with the exception of the French site. Synthesis and applications . The integration of soil microbial functional traits in the assessment of nitrogen‐related grassland ecosystem services has direct contributions for understanding sustainable management of grassland ecosystems. The fundamental aspects of this study suggest that integrating a soil microbial component in grassland management may enhance sustainability of such grass‐based agroecosystems. Abstract : The integration of soil microbial functional traits in the assessment of nitrogen‐related grassland ecosystem services has direct contributions for understanding sustainable management of grassland ecosystems. The fundamental aspects of this study suggest that integrating a soil microbial component in grassland management may enhance sustainability of such grass‐based agroecosystems.